Prospection and identification of traditional-heritage Peruvian grapevine cultivars (Vitis vinifera L.) from Ica and Cañete valleys - Mendoza Solari, Karl; Aliquo, Gustavo Alberto; Prieto, Jorge Alejandro; Blas, R.; Flores, J.; Casas, A.; Grados, M.; Aybar, M.; Torres, Maria Del Rocio (Julius Kühn-Institut Institute for Grapevine Breeding Geilweilerhof, 2022)
Interest in ancient and autochthonous cultivars has increased in recent years since they are directly related to the historical and cultural values of a region. Ica and Cañete valleys (Peru) have a long history of grapevine cultivation and the aim of this study was to identify phenotypes corresponding to the most used varieties for the local production of Pisco and wine. The 29 samples were collected in 17 vineyards in the Ica and Cañete val leys, and were analyzed using 20 molecular markers and 5 morphological descriptors according to the OIV. Results showed that the 29 collected samples corre sponded to 11 genotypes: seven traditional cultivars and four unknown genotypes not registered previously. The known cultivars were 'Muscat of Alexandria', 'Listán Prieto', 'Quebranta', 'Moscatel Rosado', 'Pedro Gimén ez', 'Muscat Hamburg' and 'Palomino Fino'. The four not registered genotypes are locally known as 'Mollar de Ica', 'Moscatel Rosada de Cañete', 'Prieta Mollar' and 'Torontel'. All of them correspond to offspring of traditional-heritage Peruvian cultivars. We also found a phenotypic variation of 'Listán Prieto' with muscat flavor and identified phenotypic berry color variations in 'Quebranta'. This study increases the knowledge of traditional Peruvian grape varieties and highlight the genetic variability preserved in the traditional vineyards of local producers.